Nano asparagus microcrystalline cellulose as well as preparation method and application thereof

Through microwave heat pump drying, vapor explosion treatment, alkaline dissolution, acid dissolution, decolorization and magnetic induction electric field-assisted extraction, high yield and high purity nano-asparagus microcrystalline cellulose were prepared, and the microcrystalline cellulose in the prior art was solved. The problem of low yield rate and poor quality, and it has excellent results in the stability of milk tea.

CN119464411AActive Publication Date: 2025-02-18AGRI INST OF AGRI JIANGXI PROVINCE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411597887.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The method of preparing microcrystalline cellulose using asparagus as raw material in the prior art has problems such as low yield, poor quality and low purity, resulting in low efficiency of asparagus waste resource utilization.

Method used

Using microwave heat pump drying and steam explosion treatment, the old stems or straws of asparagus are converted into crude fibers, and then alkaline, acid-lysis, decolorization, and auxiliary extraction in magnetic induction electric field. Finally, acid-lysis and freezing spray drying Nanoasparagus microcrystalline cellulose was obtained.

Benefits of technology

The yield and purity of nano-asparagus microcrystalline cellulose was significantly improved, the resource utilization efficiency of asparagus waste was improved, and excellent results were shown in the emulsification stability of milk tea.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127437940000091
    Figure BDA0005127437940000091
  • Figure BDA0005127437940000092
    Figure BDA0005127437940000092
Patent Text Reader

Abstract

The invention provides nano asparagus microcrystalline cellulose as well as a preparation method and application thereof, and belongs to the technical field of food processing. The method comprises the following steps: drying old asparagus stems or asparagus straws by a microwave heat pump, rehydrating, and then carrying out steam explosion treatment to obtain crude fibers; carrying out alkaline hydrolysis, acidolysis and decoloration treatment on the crude fibers to obtain hydrolysate, mixing the hydrolysate with cellulase, and carrying out magnetic induction electric field assisted extraction to obtain an extracting solution; performing acidolysis treatment on the extracting solution, filtering to obtain a solid hydrolysate, washing the solid hydrolysate, and drying to obtain the nano asparagus microcrystalline cellulose. The nano asparagus microcrystalline cellulose prepared by extracting dietary fibers from asparagus byproducts (asparagus straws or old stems) is high in yield and purity and good in quality, and the stability of the milk tea can be remarkably improved by adding the prepared microcrystalline cellulose into the milk tea.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food processing, and in particular relates to nano asparagus microcrystalline cellulose and a preparation method and application thereof. Background Art

[0002] Asparagus is a perennial herb belonging to the genus Asparagus of the Asparagaceae family. It is also known as Asparagus officinalis, Asparagus beard vegetable, and green asparagus. As a rare vegetable that can be used as both medicine and food, it is not only delicious, but also has many special nutritional and therapeutic effects. It enjoys the reputation of "King of Vegetables" in the international market. Asparagus stalks or old stems are the waste materials produced during the harvesting, packaging and quick-freezing of asparagus. Asparagus stalks or old stems are still rich in polysaccharides, dietary fiber and other biologically active ingredients. However, due to the lack of effective comprehensive utilization methods, this high-quality by-product resource has long been directly discarded except for a very small part that has been used as feed, which not only causes a huge waste of resources, but also seriously pollutes the environment.

[0003] Microcrystalline cellulose (MCC) is a linear polysaccharide substance bonded by β-1,4-glucosidic bonds. It is a white, odorless, tasteless crystalline powder composed of extremely fine short rods or powdered porous particles that can flow freely after natural cellulose is hydrolyzed by dilute acid to the limiting degree of polymerization (LODP). The particle size is generally 20-80μm, the limiting degree of polymerization is 15-375, it is non-fibrous and has strong fluidity. It is insoluble in water, dilute acid, organic solvents and oils, partially dissolves and swells in dilute alkaline solutions, and has high reactivity in carboxymethylation, acetylation and esterification processes. Due to its special properties such as low degree of polymerization and large specific surface area, microcrystalline cellulose is widely used in medicine, food, cosmetics and other industries.

[0004] However, the existing method of preparing microcrystalline cellulose using asparagus as raw material has the problems of low yield, poor quality, low purity and the like of microcrystalline cellulose. Therefore, it is urgent to provide a new method for preparing nano asparagus microcrystalline cellulose to improve the resource utilization efficiency of asparagus waste. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a nano-asparagus microcrystalline cellulose and a preparation method and application thereof, so as to overcome the problems of low yield, poor quality and low purity of microcrystalline cellulose in the existing methods.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing nano asparagus microcrystalline cellulose, comprising the following steps:

[0008] 1) Drying old asparagus stems or asparagus stalks by microwave heat pump, rehydrating and then performing steam explosion treatment to obtain crude fiber;

[0009] 2) subjecting the crude fiber to alkaline hydrolysis, acid hydrolysis and decolorization to obtain a hydrolyzate, mixing the hydrolyzate with cellulase, and performing magnetic induction electric field assisted extraction to obtain an extract;

[0010] 3) The extract is subjected to acid hydrolysis treatment and then filtered to obtain a solid hydrolyzate, and the solid hydrolyzate is washed and dried to obtain nano asparagus microcrystalline cellulose.

[0011] Preferably, the power of the microwave heat pump drying in step 1) is 300-400W, and the temperature of the microwave heat pump drying is 55-65°C.

[0012] Preferably, the pressure of the steam explosion treatment in step 1) is 1.2-1.5 MPa, and the time of the steam explosion treatment is 1-3 min.

[0013] Preferably, the amount of the cellulase in step 2) is 0.06-0.08% of the mass of the hydrolyzate;

[0014] The excitation voltage of the magnetic induction electric field is 300-500V, and the frequency of the magnetic induction electric field is 500-700Hz.

[0015] Preferably, in step 2), the alkaline hydrolysis adopts a sodium hydroxide solution with a mass concentration of 2-4%, the temperature of the alkaline hydrolysis is 80-120° C., the time is 1.0-1.5 h, the weight ratio of the old asparagus stems to the sodium hydroxide solution is 1:0.5-1.5, or the weight ratio of the asparagus stalks to the sodium hydroxide solution is 1:0.5-1.5.

[0016] Preferably, in step 2), the acid hydrolysis is performed using a hydrochloric acid solution with a mass concentration of 4-6%, and the hydrolysis is performed at 80-100° C. for 0.5-1.5 h, and the weight ratio of the old asparagus stems to the hydrochloric acid solution is 1:4-8, or the weight ratio of the asparagus stalks to the hydrochloric acid solution is 1:9-11.

[0017] Preferably, the decolorization treatment in step 2) is: first decolorize with a H2O2 solution with a mass concentration of 1.5-2.5% at 55-65°C for 0.5-1.5h, then rinse with a sodium sulfite solution with a mass concentration of 1.5-2.5% until neutral, and wash with water 1-3 times; the weight ratio of the old asparagus stems to the H2O2 solution is 1:4-6, or the weight ratio of the asparagus stalks to the H2O2 solution is 1:4-6.

[0018] Preferably, the acid hydrolysis treatment in step 3) uses a hydrochloric acid solution with a mass concentration of 6 to 9%, and hydrolyzes at 80 to 100° C. for 0.5 to 1.5 hours.

[0019] The invention also provides nano asparagus microcrystalline cellulose prepared by the preparation method.

[0020] The present invention also provides application of the nano asparagus microcrystalline cellulose in improving the emulsification stability of milk tea.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention uses asparagus byproducts as raw materials (asparagus stalks or old stems), extracts dietary fiber and prepares nano asparagus microcrystalline cellulose. Milk tea has a high solid content during the production process, and adding the prepared microcrystalline cellulose to milk tea can significantly improve its stability.

[0023] The present invention can remove moisture in asparagus stalks or old stems to the greatest extent through microwave heat pump drying, adopts steam explosion classification treatment to convert long fibers into short fibers, thereby reducing the difficulty of subsequent enzymatic hydrolysis, removes substances such as protein and fatty acids in the raw materials through alkaline hydrolysis, removes substances such as sugar, starch and pectin through acid hydrolysis, removes pigments through decolorization, and carries out the enzymatic hydrolysis and extraction process in magnetic induction electric field reaction equipment, sets different voltages and frequencies, thereby improving the extraction rate of dietary fiber, and finally obtains nano asparagus microcrystalline cellulose with high yield and purity and good quality through acid hydrolysis treatment and freeze spray drying. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing nano asparagus microcrystalline cellulose, comprising the following steps:

[0025] 1) Drying old asparagus stems or asparagus stalks by microwave heat pump, rehydrating and then performing steam explosion treatment to obtain crude fiber;

[0026] 2) subjecting the crude fiber to alkaline hydrolysis, acid hydrolysis and decolorization to obtain a hydrolyzate, mixing the hydrolyzate with cellulase, and performing magnetic induction electric field assisted extraction to obtain an extract;

[0027] 3) The extract is subjected to acid hydrolysis treatment and then filtered to obtain a solid hydrolyzate, and the solid hydrolyzate is washed and dried to obtain nano asparagus microcrystalline cellulose.

[0028] In the present invention, the old stems or asparagus stalks are dried by microwave heat pump, and steam explosion treatment is performed after rehydration to obtain crude fiber. The power of the microwave heat pump drying is preferably 300-400W, and more preferably 320-380W; the temperature of the microwave heat pump drying is preferably 55-65°C, and more preferably 58-62°C; the thinning treatment is performed before the rehydration, and the length of the old stems or asparagus stalks after the thinning treatment is preferably 3-5cm, and more preferably 3.5-4.5cm; the water content of the old stems or asparagus stalks after the rehydration treatment is preferably 40-50wt%, and more preferably 42-48wt%; the pressure of the steam explosion treatment is preferably 1.2-1.5Mpa, and more preferably 1.3-1.4Mpa; the time of the steam explosion treatment is preferably 1-3min, and more preferably 1.5-2.5min.

[0029] In the present invention, the crude fiber is subjected to alkaline hydrolysis, acid hydrolysis and decolorization to obtain a hydrolyzate, the hydrolyzate is mixed with cellulase, and an extract is obtained by magnetic induction electric field assisted extraction. The alkaline hydrolysis preferably uses a sodium hydroxide solution with a mass concentration of 2 to 4%, and the mass concentration of the sodium hydroxide solution is preferably 2.5 to 3.5%; the temperature of the alkaline hydrolysis is preferably 80 to 120°C, more preferably 90 to 110°C; the time is preferably 1.0 to 1.5h, more preferably 1.2 to 1.4h; the weight ratio of the old asparagus stems to the sodium hydroxide solution is preferably 1:0.5 to 1.5, more preferably 1:0.7 to 1.4; or the weight ratio of the asparagus stalks to the sodium hydroxide solution is preferably 1:0.5 to 1.5, more preferably 1:0.7 to 1.4. The acid hydrolysis preferably uses a hydrochloric acid solution with a mass concentration of 4-6%, and the mass concentration of the hydrochloric acid solution is 4.5-5.5%; the hydrolysis is carried out at 80-100°C for 0.5-1.5h, the hydrolysis temperature is preferably 85-95°C, and the hydrolysis time is preferably 0.7-1.4h; the weight ratio of the old asparagus stems to the hydrochloric acid solution is preferably 1:4-8, and more preferably 1:5-7; or the weight ratio of the asparagus stalks to the hydrochloric acid solution is preferably 1:9-11, and more preferably 1:9.5-10.5. The decolorization treatment is as follows: firstly, decolorize with a H2O2 solution having a mass concentration of 1.5-2.5% at 55-65°C for 0.5-1.5h, wherein the mass concentration of the H2O2 solution is preferably 1.8-2.2%; the decolorization temperature is preferably 58-62°C; the decolorization time is preferably 0.7-1.4h; then, rinse with a sodium sulfite solution having a mass concentration of 1.5-2.5% until neutral, wherein the mass concentration of the sodium sulfite solution is preferably 1.8-2.2%; wash with water 1-3 times; the weight ratio of the old asparagus stems to the H2O2 solution is preferably 1:4-6, and more preferably 1:4.5-5.5; or the weight ratio of the asparagus stalks to the H2O2 solution is preferably 1:4-6, and more preferably 1:4.5-5.5. The dosage of the cellulase is preferably 0.06-0.08% of the mass of the hydrolyzate, and more preferably 0.065-0.075%; the excitation voltage of the magnetic induction electric field is preferably 300-500V, and more preferably 350-450V; the frequency of the magnetic induction electric field is preferably 500-700Hz, and more preferably 550-650Hz.

[0030] In the present invention, the extract is subjected to acid hydrolysis treatment and then filtered to obtain a solid hydrolyzate, and the solid hydrolyzate is washed and freeze-spray dried to obtain microcrystalline cellulose. The acid hydrolysis treatment preferably uses a hydrochloric acid solution with a mass concentration of 6 to 9%, and hydrolyzes at 80 to 100°C for 0.5 to 1.5 hours; the weight concentration of the hydrochloric acid solution is preferably 7 to 8%; the hydrolysis temperature is preferably 85 to 95°C; the weight ratio of the extract to the hydrochloric acid solution is preferably 1:3 to 5, and more preferably 1:3.5 to 4.5; the hydrolysis time is preferably 0.7 to 1.4 hours; the washing uses water at 90 to 100°C to wash the solid hydrolyzate to neutrality.

[0031] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0032] Example 1

[0033] The old asparagus stems are dried by a microwave heat pump at a power of 350 W and a temperature of 60° C. The dried old asparagus stems are cut into a length of 4 cm and rehydrated, wherein the water content of the old asparagus stems after rehydration is 45 wt %. The rehydrated old asparagus stems are placed in a steam explosion reaction device for steam explosion treatment, wherein the pressure of the steam explosion treatment is 1.4 Mpa and the time is 2 min to obtain crude fiber.

[0034] The crude fiber is placed in a sodium hydroxide solution for alkaline hydrolysis, wherein the weight concentration of the sodium hydroxide alkaline boiling solution is 3%, the temperature is 100°C, the time is 1.3 hours, and the weight ratio of the old asparagus stems to the sodium hydroxide solution is 1:1; after the alkaline hydrolysis, a hydrochloric acid solution with a weight concentration of 5% is added, and hydrolysis is carried out at 90°C for 1 hour; the weight ratio of the old asparagus stems to the hydrochloric acid solution is 1:6; after the acid hydrolysis, it is first treated with a H2O2 solution with a weight concentration of 2% at 60°C for 1 hour for decolorization; the weight ratio of the old asparagus stems to the H2O2 solution is 1:5; then it is rinsed with a sodium sulfite solution with a weight concentration of 2% to neutrality, washed with water twice to obtain a hydrolyzate, the hydrolyzate is mixed with 0.07% cellulase by mass of the hydrolyzate, and then input into a magnetic induction electric field reaction device at a flow rate of 0.5L / min for auxiliary extraction to obtain an extract; the excitation voltage of the magnetic induction electric field reaction device is 400V, and the frequency of the magnetic induction electric field is 600Hz.

[0035] The extract and 8% hydrochloric acid solution were mixed in a weight ratio of 1:4, and hydrolyzed at 90°C for 1 hour. The hydrolyzate was rapidly cooled, filtered with a sand core funnel, and the solid hydrolyzate was fully washed with 1L of 95°C hot water until it was neutral. The solid hydrolyzate was collected and dried to obtain nano-asparagus microcrystalline cellulose.

[0036] Example 2

[0037] The old asparagus stems are subjected to microwave heat pump drying at a power of 300 W and a temperature of 55° C. The dried old asparagus stems are cut into a length of 3 cm and rehydrated, wherein the water content of the old asparagus stems after rehydration is 40 wt %. The rehydrated old asparagus stems are placed in a steam explosion reaction device for steam explosion treatment, wherein the pressure of the steam explosion treatment is 1.2 Mpa and the time is 1 min to obtain crude fiber.

[0038] The crude fiber is placed in a sodium hydroxide solution for alkaline hydrolysis, wherein the weight concentration of the sodium hydroxide alkaline boiling solution is 2%, the temperature is 80°C, the time is 1.0h, and the weight ratio of the old asparagus stems to the sodium hydroxide solution is 1:0.5; after the alkaline hydrolysis, a hydrochloric acid solution with a weight concentration of 4% is added, and the hydrolysis is carried out at 80°C for 0.5h; the weight ratio of the old asparagus stems to the hydrochloric acid solution is 1:4; after the acid hydrolysis, the asparagus stems are first decolorized by treating with a H2O2 solution with a weight concentration of 1.5% at 55°C for 0.5h; the weight ratio of the old asparagus stems to the H2O2 solution is 1:4; then the asparagus stems are rinsed with a sodium sulfite solution with a weight concentration of 1.5% to neutrality, washed with water once to obtain a hydrolyzate, the hydrolyzate is mixed with 0.06% of the mass of the hydrolyzate, and then input into a magnetic induction electric field reaction device at a flow rate of 0.5L / min to assist in extraction to obtain an extract; the excitation voltage of the magnetic induction electric field reaction device is 300V, and the frequency of the magnetic induction electric field is 500Hz.

[0039] The extract and a 6% hydrochloric acid solution were mixed in a weight ratio of 1:3, and hydrolyzed at 80°C for 0.5h. The hydrolyzate was rapidly cooled, filtered with a sand core funnel, and the solid hydrolyzate was fully washed with 1L of 90°C hot water until it was neutral. The solid hydrolyzate was collected and dried to obtain nano-asparagus microcrystalline cellulose.

[0040] Example 3

[0041] The old asparagus stems are subjected to microwave heat pump drying at a power of 400 W and a temperature of 65° C. The dried old asparagus stems are cut into a length of 5 cm and rehydrated, wherein the water content of the old asparagus stems after rehydration is 50 wt %. The rehydrated old asparagus stems are placed in a steam explosion reaction device for steam explosion treatment, wherein the pressure of the steam explosion treatment is 1.5 Mpa and the time is 3 minutes to obtain crude fiber.

[0042] The crude fiber is placed in a sodium hydroxide solution for alkaline hydrolysis, wherein the weight concentration of the sodium hydroxide alkaline boiling solution is 4%, the temperature is 120°C, the time is 1.5 hours, and the weight ratio of the old asparagus stems to the sodium hydroxide solution is 1:1.5; after the alkaline hydrolysis, a hydrochloric acid solution with a weight concentration of 6% is added, and hydrolysis is carried out at 100°C for 1.5 hours; the weight ratio of the old asparagus stems to the hydrochloric acid solution is 1:8; after the acid hydrolysis, it is first treated with a H2O2 solution with a weight concentration of 2.5% at 65°C for 1.5 hours for decolorization; the weight ratio of the old asparagus stems to the H2O2 solution is 1:6; then it is rinsed with a sodium sulfite solution with a weight concentration of 2.5% to neutrality, washed with water 3 times to obtain a hydrolyzate, the hydrolyzate is mixed with 0.08% of the mass of the hydrolyzate, and then input into a magnetic induction electric field reaction device at a flow rate of 0.5L / min to assist in extraction to obtain an extract; the excitation voltage of the magnetic induction electric field reaction device is 500V, and the frequency of the magnetic induction electric field is 700Hz.

[0043] The extract and a 9% hydrochloric acid solution were mixed in a weight ratio of 1:5, and hydrolyzed at 100°C for 1.5 hours. The hydrolyzate was rapidly cooled, filtered with a sand core funnel, and the solid hydrolyzate was fully washed with 1L of 100°C hot water until it was neutral. The solid hydrolyzate was collected and dried to obtain nano-asparagus microcrystalline cellulose.

[0044] Experimental Example 1

[0045] Effects of different drying methods on the dehydration rate of old asparagus stems

[0046] The specific process is as follows:

[0047] Eight groups, A, B, C, D, E, F, G, and H, were set up, and the old stems of asparagus were dried to constant weight under different drying methods, and their moisture content was measured with a moisture meter, and the dehydration rate = 1-moisture content. Among them, A was dried according to the method of Example 1; B was dried according to the method of Example 2; C was dried according to the method of Example 3; D was dried in a microwave vacuum: the microwave power was 600W, followed by hot air drying, and the hot air drying temperature was 80°C; E was dried by microwave heat pump at a power of 250W and a temperature of 60°C; F was dried by microwave heat pump at a power of 450W and a temperature of 60°C; G was dried by microwave heat pump at a power of 350W and a temperature of 50°C; H was dried by microwave heat pump at a power of 350W and a temperature of 70°C.

[0048] Experimental results: as shown in Table 1.

[0049] Table 1 Effect of different drying methods on the dehydration rate of old asparagus stems

[0050] deal with Dehydration rate% A 95.16 B 94.65 C 95.01 D 89.34 E 73.24 F 78.67 G 69.76 H 75.19

[0051] It can be seen from Table 1 that microwave heat pump drying is more suitable for dehydration and drying of old asparagus stems than microwave hot air drying. When using microwave heat pump drying, excessive or low microwave power and temperature will lead to poor dehydration efficiency, which is not conducive to subsequent steam explosion treatment.

[0052] Experimental Example 2

[0053] Effects of different magnetic induction electric field reaction conditions on the extraction of insoluble dietary fiber from old asparagus stems

[0054] Seven groups, A, B, C, D, E, F, and G, were set up. The extract obtained by auxiliary extraction of old asparagus stems under different reaction conditions of magnetic induction electric field was dried to constant weight at 105°C, crushed, and weighed to obtain insoluble dietary fiber. The insoluble dietary fiber extraction rate (%) = insoluble dietary fiber (g) / dry weight of old asparagus stems (g). Among them, A was extracted according to the method of Example 1; B was extracted according to the method of Example 2; C was extracted according to the method of Example 3; D changed the excitation voltage of the magnetic induction electric field in Example 1 to 250V; E changed the excitation voltage of the magnetic induction electric field in Example 1 to 550V; F changed the frequency of the magnetic induction electric field in Example 1 to 450Hz; G changed the frequency of the magnetic induction electric field in Example 1 to 550Hz.

[0055] Experimental results: as shown in Table 2.

[0056] Table 2 Extraction rate of insoluble dietary fiber from old asparagus stems under different magnetic induction electric field reaction conditions

[0057] deal with Extraction rate % A 69.89 B 69.76 C 69.81 D 48.13 E 45.62 F 50.04 G 49.13

[0058] It can be seen from Table 2 that appropriately increasing the excitation voltage and frequency of the magnetic induction electric field can greatly improve the extraction rate of insoluble dietary fiber, but too high an excitation voltage and frequency will inhibit the enzymatic hydrolysis of cellulose.

[0059] Experimental Example 3

[0060] Performance measurement of nano-asparagus microcrystalline cellulose prepared in Examples 1 to 3

[0061] 1. Calculate the yield of nano-asparagus microcrystalline cellulose.

[0062] The yield of nano-asparagus microcrystalline cellulose / %=the mass of microcrystalline cellulose / the mass of insoluble dietary fiber in old asparagus stems×100%.

[0063] 2. Determination of degree of polymerization (DP) of nano-asparagus microcrystalline cellulose

[0064] Weigh 0.900g of water-free nano-asparagus microcrystalline cellulose sample to an accuracy of 0.5mg, place it in a 30mL dissolution bottle, add 15mL of distilled water and 7 copper sheets, press the bottle stopper tightly and shake it vigorously to disperse the sample, then measure 15mL of copper ethylenediamine solution and put it into the bottle, and remove the air in the bottle by adding glass beads, plug the stopper and put it in a reciprocating oscillator to oscillate for about 15 minutes. After the sample is completely dissolved, put the dissolution bottle into a viscometer to test the solution outflow time, find out the intrinsic viscosity value through the calculated relative viscosity, and calculate the average degree of polymerization according to formula I.

[0065] DP 0.905 =0.75[η] (Formula I)

[0066] In formula I: DP-average degree of polymerization;

[0067] [η]-intrinsic viscosity value.

[0068] 3. Determination of Carbohydrates in Nano-Asparagus Microcrystalline Cellulose

[0069] Accurately weigh about 100 mg of nano-asparagus microcrystalline cellulose sample, transfer it completely to a 250 mL conical flask with 20 mL of distilled water, add 50 mL of 0.5 mol / L potassium dichromate solution, shake well, slowly add 100 mL of concentrated sulfuric acid along the wall, heat to a slight boil, transfer to a 250 mL volumetric flask after cooling to room temperature, dilute with water, and mix well. Use a pipette to measure 5 mL of the treatment solution, add 1 drop of o-phenanthroline-ferrous indicator solution, titrate with a calibrated ammonium ferrous sulfate standard solution (0.1 mol / L), and record the consumed volume. Titrate the blank at the same time. Calculate the carbohydrate content in nano-asparagus microcrystalline cellulose according to formula II.

[0070]

[0071] In formula II: ω is the carbohydrate content of nano-asparagus microcrystalline cellulose, %;

[0072] V1-consumption volume of ammonium ferrous sulfate during blank titration, mL

[0073] V2-the volume of ammonium ferrous sulfate consumed when titrating the sample solution, mL

[0074] c-Concentration of ammonium ferrous sulfate standard solution, mol / L

[0075] m-mass of microcrystalline cellulose sample, g

[0076] 4. X-ray diffraction analysis of microcrystalline cellulose

[0077] Instrument parameters: copper target X-ray tube, LynxEye array detector, tube power: 2.2kW, scanning mode: / goniometer, angle accuracy: 0.001°, angle range 10-90°. The prepared nano-asparagus microcrystalline cellulose was placed in a circular sample slot, flattened with a glass sheet, and placed in the instrument for testing.

[0078] The crystallinity index was calculated according to the formula.

[0079]

[0080] In formula III: ICr represents the crystallinity index,

[0081] I 002 Represents the maximum diffraction intensity of the 002 surface,

[0082] I am Represents the diffraction intensity of the amorphous region.

[0083] Experimental results: as shown in Table 3.

[0084] Table 3 Performance test results of nano asparagus microcrystalline cellulose prepared in Examples 1 to 3

[0085] deal with Yield % Degree of Polymerization Carbohydrate content % Crystallinity % Example 1 53.18 86.64 108.91 70.03 Example 2 51.89 84.72 106.33 69.15 Example 3 52.97 85.97 107.45 68.34

[0086] As shown in Table 3, the degree of polymerization affects the yield of microcrystalline cellulose products. The smaller the degree of polymerization, the greater the probability that macromolecular cellulose is degraded into glucose. The carbohydrate content is the main indicator for judging the purity of microcrystalline cellulose. It can be seen that the nano-asparagus microcrystalline cellulose prepared in Examples 1 to 3 has a high yield, good quality and high purity.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing nano asparagus microcrystalline cellulose, characterized in that: The following steps are involved: 1) Drying old asparagus stems or asparagus stalks by microwave heat pump, rehydrating and then performing steam explosion treatment to obtain crude fiber; 2) subjecting the crude fiber to alkaline hydrolysis, acid hydrolysis and decolorization to obtain a hydrolyzate, mixing the hydrolyzate with cellulase, and performing magnetic induction electric field assisted extraction to obtain an extract; 3) The extract is subjected to acid hydrolysis treatment and then filtered to obtain a solid hydrolyzate, and the solid hydrolyzate is washed and dried to obtain nano asparagus microcrystalline cellulose.

2. The preparation method according to claim 1, characterized in that: Step 1) The power of the microwave heat pump drying is 300-400W, and the temperature of the microwave heat pump drying is 55-65°C.

3. The preparation method according to claim 1, characterized in that: Step 1) The pressure of the steam explosion treatment is 1.2-1.5 MPa, and the time of the steam explosion treatment is 1-3 min.

4. The preparation method according to claim 1, characterized in that: Step 2) The amount of the cellulase used is 0.06-0.08% of the mass of the hydrolyzate; The excitation voltage of the magnetic induction electric field is 300-500V, and the frequency of the magnetic induction electric field is 500-700Hz.

5. The preparation method according to claim 1, characterized in that: Step 2) The alkaline hydrolysis adopts a sodium hydroxide solution with a mass concentration of 2-4%, the temperature of the alkaline hydrolysis is 80-120° C., the time is 1.0-1.5 h, the weight ratio of the old asparagus stems to the sodium hydroxide solution is 1:0.5-1.5, or the weight ratio of the asparagus stalks to the sodium hydroxide solution is 1:0.5-1.

5.

6. The preparation method according to claim 1, characterized in that: Step 2) The acid hydrolysis is carried out at 80-100° C. for 0.5-1.5 h using a hydrochloric acid solution having a mass concentration of 4-6%, wherein the weight ratio of the old asparagus stems to the hydrochloric acid solution is 1:4-8, or the weight ratio of the asparagus stalks to the hydrochloric acid solution is 1:9-11.

7. The preparation method according to claim 1, characterized in that: Step 2) The decolorization treatment is: first decolorize with a H2O2 solution with a mass concentration of 1.5-2.5% at 55-65°C for 0.5-1.5h, then rinse with a sodium sulfite solution with a mass concentration of 1.5-2.5% until neutral, and wash with water 1-3 times; the weight ratio of the old asparagus stems to the H2O2 solution is 1:4-6, or the weight ratio of the asparagus stalks to the H2O2 solution is 1:4-6.

8. The preparation method according to claim 1, characterized in that: Step 3) The acid hydrolysis treatment uses a hydrochloric acid solution with a mass concentration of 6-9% and is hydrolyzed at 80-100° C. for 0.5-1.5 hours.

9. Nano-asparagus microcrystalline cellulose prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nano asparagus microcrystalline cellulose according to claim 9 in improving the emulsification stability of milk tea.

Citation Information

Patent Citations

  • Method for preparing microcrystalline cellulose of asparagus by applying asparagus stalks

    CN105747237A

  • Detection pretreatment method for protein sample enzymolysis assisted by induced electric field

    CN115433755A

  • Cereal sample hydrolysis pretreatment method

    CN115505613A

  • Induced electric field-based multi-magnetic path, multi-stage fluid reaction system and application thereof

    WO2019056401A1